Pemulihan Warisan Budaya: Desain Laboratorium Filologi sebagai Pusat Pembelajaran Manuskrip Keislaman Jawa Pesisir di Fakultas Ushuluddin, Adab, dan Dakwah UIN Sayyid Ali Rahmatullah Tulungagung - Syafaah, Darisy; Rohmah, Nurul Baiti; Rejo, Uman (HUMANIKA, 2024)
This scientific study aims to explore, express, and reveal a prototype design for the philology laboratory at the Faculty of Ushuluddin, Adab, and Dakwah, UIN Sayyid Ali Rahmatullah Tulungagung campus, as a learning resource for coastal Javanese Islamic manuscripts. To realize this mission, this study was designed using research and development (R & D), while the development model used ADDIE, namely analysis, design, development, implementation, and evaluation. The results and discussion are as follows:. First, the Philology Laboratory space is designed with a contemporary, modern concept, prioritizing comfort, a more specific/special space, all-technological and contextual. Second, the position of space in the design of the Philology Laboratory has been arranged by the concept of andragogy, or adult learning. Third, this special space design is prepared as a bridge for gathering and meeting people who study coastal Javanese Islamic manuscripts, a research center, and a reference source regarding ancient Islamic manuscripts. Fourth, the response from fellow lecturers and students was very positive regarding the design for developing this philology laboratory.